How Religiosity Helps Couples Prevent, Resolve, and Overcome Marital Conflict. - Lambert, Nathaniel M.; Dollahite, David C. (Family Relations, 2006)
This study reports on in-depth interviews with 57 highly religious, middle-aged married couples representing the major Abrahamic faiths (Christianity, Judaism, Islam) residing in New England and Northern California. The study uses grounded theory methods to create themes and a model describing the ways that religiosity influences marital conflict. Couples reported that religiosity affects the conflict in their marriage at three phases of the conflict process: (a) problem prevention, (b) conflict resolution, and (c) relationship reconciliation. Practitioners may assist religious couples that are struggling with marital conflict by encouraging them to look to religious beliefs and practices. Reprinted by permission of the publisher.